Achieving sustainable campus through integrated project delivery in northern region higher education institution - Syukran, Abdul Rahim (2017)
The sustainability commitment of a nation can be reflected in how much attention is given to the sustainability development of youth and future leaders. Higher Education Institutions (HEIs) are one of the main players in producing the nation's future leaders by emulating the sustainability agenda into the curriculum and physical infrastructures. Therefore, it is crucial that sustainable campuses are designed to fulfil the educational needs of these future leaders. However, due to the nature of construction development, campuses are being developed in the traditional methods which are burdened by many challenges such as project delay, fragmented processes and high construction waste. To overcome these challenges, many scholars have proposed the Integrated Project Delivery (IPD) as a method that is beneficial for sustainable development. Accordingly, this research investigated a novel approach to sustainable campus development by identifying how IPD can be applied in the physical development of campuses specifically within the Malaysian northern region HEIs. Semi-structured interviews were conducted with 6 participants who were the experts or main decision- makers in the respective HEIs. The qualitative data was analysed using the Template Analysis method with the aid of Nvivo 10 software. The findings indicate that although the participants were aware of the importance of sustainability development, most of them were unfamiliar with most of the IPD practices in campus development. Nevertheless, some of the IPD practices were applied by the participants. The guideline developed at the end of this research highlights the current practices which overlap the IPD principles and suggests the additional aspects of IPD that can be merged with sustainable campus development activities. Some limitations of the study are also indicated, suggesting opportunities for future research.